GERAKAN GOTONG ROYONG DAN PARTISIPASI MAHASISWA DALAM MENINGKATKAN KEBERSIHAN KAMPUS - Uswatun Chasanah; Fatih Arsyad Dharmawan; Eli Masnawati; M. Sifa Yulianis; Amir Bandar Abdul Majid (Jurnal Pengabdian Masyarakat Sabangka, 2026)
mutual cooperation movement within the environment of Sunan Giri University Surabaya has been successfully carried out by scholarship students and also involves the community in this mutual cooperation movement. Good collaboration between students and the community has enabled positive outcomes. This mutual cooperation movement includes cleaning the environment, addressing waste management issues, and raising awareness about the importance of cleanliness. Active involvement of students is key to the success of this program. This mutual cooperation program also serves as a learning opportunity for students to develop social skills and leadership. This study aims to analyze the role of the mutual cooperation movement and student participation in improving campus cleanliness using the Asset-Based Community Development (ABCD) approach. Theresearch method used is qualitative with data collection techniques through observation, interviews, and documentation. The Asset-Based Community Development (ABCD) approach is applied to identify assets and resources owned by the campus community as capital to encourage active student participation in cleanliness activities. The results show that optimizing community assets through mutual cooperation significantly increases awareness and participation of students in maintaining campus environmental cleanliness. The implications of this study emphasize the importance of asset-based empowerment in building collective awareness to create a clean and sustainable campus environment.